2017
DOI: 10.3389/fneur.2017.00362
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Cerebellar Edema Subsequent to Accidental Prescription Opioid Intoxication in Children

Abstract: We present two recent cases of toddlers who developed malignant cerebellar edema subsequent to accidental ingestion of prescription opioids. Both children presented acute neurological decline, hydrocephalus, and tonsillar herniation requiring emergent ventricular drain placement, suboccipital craniectomy, and partial cerebellectomy. Together with several other reports, these cases suggest the existence of an uncommon yet severe syndrome of acute opioid-induced malignant cerebellar edema. We hypothesize that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…There are also patients in the literature who received only supportive care, such as the patient described by Nanan et al [12] who had similar neurologic outcomes to our patient with significant impairment. That is in contrast to Reisner et al [3], Mills et al [8], and Duran et al, [13] who also illustrated similar neurologic outcomes after undergoing more invasive neurosurgical interventions with decompressive craniotomy, and in once case cerebellectomy. Devastating neurologic outcomes or death, as described by Krinsky and Reischard et al [2], Shrot et al [5], Riascos et al [9], and Metkees et al [10], and are also described, and hoped to be mitigated by early neuro-surgical interventions as were undertaken with our patient.…”
Section: Prognosis and Outcomesmentioning
confidence: 55%
See 3 more Smart Citations
“…There are also patients in the literature who received only supportive care, such as the patient described by Nanan et al [12] who had similar neurologic outcomes to our patient with significant impairment. That is in contrast to Reisner et al [3], Mills et al [8], and Duran et al, [13] who also illustrated similar neurologic outcomes after undergoing more invasive neurosurgical interventions with decompressive craniotomy, and in once case cerebellectomy. Devastating neurologic outcomes or death, as described by Krinsky and Reischard et al [2], Shrot et al [5], Riascos et al [9], and Metkees et al [10], and are also described, and hoped to be mitigated by early neuro-surgical interventions as were undertaken with our patient.…”
Section: Prognosis and Outcomesmentioning
confidence: 55%
“…There is a paucity of literature describing varying degrees of multi-organ involvement and neurologic sequelae secondary to opiate ingestion. Although children who presented with low GCS with toxic leukoencephalopathy who recovered with mild or no neurologic deficits have been described [6, 11, 12, 13, 14, 15], we believe that these patients likely presented earlier after ingestion. Earlier access to supportive care in these cases likely lessened the effects of more sustained hypoxic injury that led to worse neurologic injury and multi-organ injury in our patient.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To the authors' knowledge, there are nine such cases reported in the literature (summarised in Table 1). 2,[6][7][8][9][10][11] These patients presented with varying symptoms. With opiate prescriptions on the rise, it is imperative to be aware of this clinical condition.…”
Section: Oxycodone Leukoencephalopathymentioning
confidence: 99%